Improvement In Status Of Tribal Women With Special Reference To The Socio-Economic Conditions: A Study In Jammu And Kashmir - Rafi Paray, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Tribals are groups that are selected for special security and each group has its own history, heritage and lifestyle. People who have been alienated by mainstream Hindu population. These communities have distinct social setup than mainstream Hindu society. In all, 8.6% of the population of India are ST, but in Jammu and Kashmir, ST is 11.9% of the population. Indian women are said to be less discriminated against than women in general. Tribal women experience greater equality and have a higher sex ratio than conventional societies. Child marriage and dowry traditions are not present in several tribals. Women are granted more equality in many tribes. A girl is never required to marry and there is more independence in matters of divorce and polyandry is found to be occurring in many tribes. Participation rates are strong as both men and women work. Dowry is becoming widespread among the indigenous tribes. In Jammu and Kashmir, tribal people are best positioned in some ways, but worse in others. Dowry and female literacy indicate that there is a mythical status linked to tribal women. Female literacy in J&K is abysmally poor. 37.54% of females cannot read and write compared to 11% of tribal women. Scheduled Tribe women work a lot more in rural areas but they do not work as frequently in urban areas. Educational achievement among tribal women is very poor from the very beginning. Tribal women who do not have an education are popular in all cultures. The paper addresses women in J&K in selected education, labor force attendance, family spending, age of marriage, and head of household position. This analysis depends on both primary and secondary results.